Pattern of Labour in Primigravidae Monitored By Partograph - Das, Suchanda; Chowdhury, Bidhan Roy; Begum, Rokeya (Journal of Chittagong Medical College Teachers’ Association, 2015)
This is a cross sectional observational study was done on 100 full term primigravidae admitted in Gyane & Obstetrics department of Bangabandhu Sheikh Mujib Medical University and Dhaka Medical College Hospital. The study was carried out during the period from 1st August 2004 to 30th January 2005. Their labour was assessesd by modified World Health Organisation (WHO) partograph. The main objective of the study was to assess the importance of pantographic contral of labour in preventing prolong labour and its consequences. 74% of these labour had spontaneous vaginal delivery, 4% required forceps delivery and 6% needed ventouse delivery, Caesarean section was done in 16% cases. It has found that 86% of the patients were delivered within 7 hrs and all patients were delivered within 12 hours from active phase of labour. There was no maternal and neonatal mortality because of close intranatal care. There was no perinatal mortality in this series. If any deviation from normal, intervention was done immediately. Because of use of partograph unnecessary intervention were also reduced. Patient with non engaged head in labour required more intervention. Majority of patients within alert line delivered vaginally but 100% of the patient crossing the action line required interference. Each and every labouring woman should be supervised by a partograph. But its use in our country still limited to medical college hospital and some district hospitals only. As the poor developing country where Maternal Mortality Rate (MMR) is so high, the use of partograph is essentials and must be used by paramedics/midwives/ nurses, which will guide them for referral in proper time. JCMCTA 2015 ; 26 (1) : 30-34